Age is just a number: long‐lasting T‐cell immunity can span several lifetimes. Issue 5 (5th March 2023) - Freen‐van Heeren, Julian J; Opstelten, Rianne
Abstract : T‐cell memory is considered long‐lasting, but new evidence recently published in Nature by Soerens et al . shows that, under certain conditions, mouse memory T‐cell immunity can span several mouse lifetimes.